Cultivating Compassion: Rohis as a Strategic Medium for Internalizing Islamic Values and Constructing Anti-Bullying Behavior in Indonesian Public Schools - Fitri Meidasari; Ahmad Sukandar (Journal of Science and Education (JSE), 2026)
Bullying remains a pervasive pathology within secondary education, necessitating interventions that transcend punitive measures and address the root moral vacuity. This study investigates the role of Islamic Spiritual Activities (Rohis) as a strategic medium for internalizing Islamic values to construct anti-bullying behaviors at SMP Negeri 1 Lemahabang and SMP Negeri 2 Karawang Timur. Employing a qualitative case study design, data were gathered through in-depth interviews, participant observation, and documentation. The study reveals that Rohis functions not merely as an extracurricular entity but as a dynamic ecosystem for moral conditioning. The findings indicate a tripartite mechanism of internalization: (1) cognitive enlightenment through theological literacy, (2) affective engagement through spiritual mentorship, and (3) conative actualization through social advocacy. The integration of values such as empathy (ta’awun) and mutual respect significantly reduces aggressive tendencies. The study concludes that Rohis serves as a vital subsystem in school ecology, transforming religious rituals into social ethics, thereby creating a compassionate shield against peer violence. These findings advocate for the elevation of spiritual organizations from peripheral activities to central pillars of character education policy.